Antimicrobial of Grape Skin (Vitis vinivera) infusum on Salivary Mutans Streptococci - Manggiasih Metaliri; Sri Utami; Hedijanti Joenoes (Faculty of Dentistry, Universitas Indonesia, 2013)
Dental caries was caused by Streptococcus mutans. Grape (Vitis vinifera) variety Blue Probolinggo have active substance: Polyphenol compound such as flavonoid, tannin, anthocyanin and resveratrol. One of its benefits is its capability to prevent dental caries. Objectives: The aim of this study was to determine the sensitivity of grape skin (Vitis vinifera) infusum on salivary mutans streptococci. Methods: Grape skin infusum of Vitis vinifera containing polyphenol compound was examined in vitro on the bacterial growth by determining the inhibition zone (agar diffusion method), Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The microorganisms tested of mutans of Streptococcus mutans was isolated from human harboring species in Jakarta Indonesia. Data obtained was done in a descriptive method. Results: Grape skin infusum containing Vitis vinifera had effect on all of mutans of Streptococcus mutans: Inhibitory zone was inclined from 0.05 mm in conentration 20%/ml to 6.70 mm in concentration 90%. MIC was made at 50% and MBC ws made at 60%. Conclusion: The grape skin of Vitis vinifera showed antimicrobial activity against locals trains of mutans of Streptococcus mutans, isolated from humans harboring species. It is expected that in can be used in preventing caries risk in the future. DOI: 10.14693/jdi.v17i1.109